Assessing the Rights of Women Victims of Home Violence During the COVID-19 Pandemic - Bagas Ragil Wicaksono, Muhammad; Lestari, Ayu (Universitas Negeri Semarang, 2020)
Domestic violence is violence that occurs in the family home, be it physical, psychological, verbal, sexual or economic violence that has legal consequences. Most of the cases of domestic violence victims are dominated by women, this is motivated by the strength of a patriarchal culture that dominates the culture and values of society. Without realizing it, this culture has silenced women's human rights. Especially in the midst of the Covid-19 pandemic because of psychological and economic pressures, it opens up great opportunities for women to become targets of objects of domestic violence. Therefore this research will further study women's human rights, protection and recovery of women victims of domestic violence. The writing of this article applies a normative juridical approach with literature study while the data management is carried out in a qualitative descriptive manner. The results of this study conclude that the protection and restoration and fulfillment of the human rights of women victims of domestic violence are still weak.